Geoconservation as an emerging geoscience - Henriques, Maria Helena (2011)
The main purpose of geoconservation is theconservation of geosites as basic units of the geological heritage through the implementation of specific inventory,evaluation, conservation, valuation and monitoring proce-dures. In this paper, geoconservation is characterised as anemergent geoscience within the Earth and Space Sciences where its scope and methods, as well as production andvalidation of knowledge can be recognised–thus definingBasic Geoconservation–, interrelations with other earth sciences can be established–thus supporting Applied Geo-conservation–, and Technical Applications of Geoconser-vation can be identified through the production of materials,methods and/or scientific services useful to society, namely geoeducation. Promoting scientific education relevant to sustainable development requires new educational approaches involving the Earth Sciences, namely through geoconservation, in order to provide citizens with tools toface environmental problems, such as those arising from the depletion of geological resources—which seriously threaten the geological heritage of the Earth—and the information,skills and will make forward-looking choices, like support-ing the legal protection of Natural Monuments and/or the implementation of geotourism (including geoparks).